FIVE YEARS ON: A COHORT STUDY OF YOUNG PEOPLE TREATED WITH ANTIPSYCHOTIC DRUGS WHO WERE TRANSITIONING FROM CHILD TO ADULT MENTAL HEALTH SERVICES IN THE LOMBARDY REGION, ITALY. Issue 1 (14th December 2015) - Reale, Laura; Clavenna, Antonio; Campi, Rita; Cartabia, Massimo; Bonati, Maurizio
Abstract : The aim of this study was to monitor the pattern of service attendance and antipsychotic use in youth with psychiatric disorders crossing age boundaries for paediatric mental health services. Regional administrative health databases were used to identify subjects born in the 1989–1992 period, who were hospitalised for psychiatric disorders and had both outpatient visits and antipsychotic prescriptions between the age of 16 and 17 years. Information about service use, antipsychotic medication, and hospitalizations during the transition period covering the age of 18–20 years was collected. A total of 144 patients were identified. Risperidone was the most commonly prescribed drug (28% of youths), followed by haloperidol (22%) and olanzapine (19%). In early adulthood, 117 of 144 (81%) subjects were still attending a mental health service: 43% of whom were receiving parallel care, and 47 (40%) of whom were being seen by adult, and 20 (17%) by child, psychiatrists. In all, 99 of 144 (69%) continued antipsychotic treatment into adulthood, 65 of whom (66%) switched to another drug, with an increase in aripiprazole, and a reduction of haloperidol and chlorpromazine, prescriptions. Less than half (45%) were re-admitted for psychiatric disorders, mainly for schizophrenia. In conclusion, only 4 out of 10 adolescents completed the transition to adult services by the age of 20 years, while 30% discontinued drug therapy and only a third maintained the treatment received during adolescence. Monitoring therapeutic pathways in this challenging life period is essential, and further analyses on the impact of service transition on pharmacological treatment are ongoing.